Esterification of chalcone derivatitives for potential liquid crystal properties - Ling, Yok Ung (Universiti Malaysia Sarawak (UNIMAS), 2010)
Chalcones have been reported having various biological actlvltles such as antitumour, antimalarial and antibacterial. However. studies also reported that they also show photochemical properties. A series of chalcone derivatives were synthesized using ClaisenSchmidt condensation. These chalcone derivatives were further reacted with isophthaloyl chloride to form an ester with 2 chalcone units for banana-shaped liquid crystal properties. However, the esterification between chalcone derivatives and benzene-I,3-dicarbonyl dichloride or isophthaloyl dichloride were not successful after several attempts.